دراسة تنبؤية لاستهلاك الكهرباء باستخدام منهجية بوكس - جينكيز دراسة حالة وكالة سونلغاز بالمسيلة للفترة 2016-2023 - أمل حرايز (My University, 2024)
This study aims to predict electric energy consumption based on data provided by Sonelgaz in the M'Sila province during the period (2016-2023) using the Box-Jenkins methodology for time series analysis. To achieve the study's objectives, the descriptive analytical method was employed, which helps in describing the study variables and analyzing the results of the applied aspect. In this study, we used the EViews 10 software to estimate the optimal model that aids in the prediction process. The study found that the best model explaining the behavior of electric energy consumption in the M'Sila province is the ARMA (4,4) model. The prediction results showed a significant convergence between the values estimated by the agency and the values obtained .
Keywords: Keywords: prediction; electricity; electric energy; Box-Jenkins methodology; M'Sila province; Sonelgaz agency; time series.